Hukum Perizinan Lingkungan sebagai Instrumen Pencapaian Sustainable Development Goals - Lizy Marchelina Butarbutar (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humani..., 2026)
Environmental licensing law plays a strategic role as a development control instrument in supporting the achievement of Sustainable Development Goals. This study aims to analyze the regulation of environmental licensing law within the framework of sustainable development, examine the role of environmental licensing in supporting the achievement of Sustainable Development Goals, and formulate an integration model of environmental licensing law based on Sustainable Development Goals as an environmental policy innovation. This research employs normative legal research using statutory, conceptual, and comparative approaches. The results indicate that environmental licensing regulations in Indonesia, through Law Number 32 of 2009, the Job Creation Law, and Government Regulation Number 22 of 2021, have integrated sustainable development principles through Environmental Impact Assessment (EIA), Environmental Management and Monitoring Efforts (UKL-UPL), and environmental approvals. The implementation of environmental licensing is directly related to the achievement of SDGs, particularly in water resource protection, climate change mitigation, and ecosystem preservation. However, challenges remain, including weak supervision, limited institutional capacity, and minimal public participation. This study proposes an integration model of environmental licensing law based on Sustainable Development Goals through regulatory strengthening, sustainable environmental governance, and integration of SDGs indicators into licensing processes. This model is expected to enhance the effectiveness of environmental licensing law as an innovative instrument to support sustainable development in a systematic and sustainable manner.